Electronic Extortion through Social Networks and its Social Risks on Jordanian Women: A Field Study - Nejadat, Ali; Bani Salim, Saad (Dirasat: Human and Social Sciences, 2024)
Objectives: The study aims to identify the forms of electronic extortion and its justifications through social media and the social risks it poses to Jordanian women. Methodos: This study falls under descriptive research utilizing a survey-based approach for data collection and information gathering. The study population consisted of all women who have experienced electronic extortion from various regions of the Hashemite Kingdom of Jordan. The survey was distributed via "Google Forms" to a sample of 303 individuals. Results: The study found that sexual extortion is the most common form of extortion experienced by Jordanian women, with an average score of (2.37 ± 0.73), followed by utilitarian extortion in the second place (2.22 ± 0.74). The main justifications that drive the extortionist to victimize the target include excessive trust in social media users (2.78 ± 0.50) and communicating with unknown individuals and exchanging friendships with them (2.76 ± 0.49). The study also identified the most significant social risks of electronic extortion on women, including jeopardizing their social future and causing them significant family and social suffering (2.75 ± 0.52) and online enticement, fraud, and cyber scams (0.71 ± 0.57). Conclusions: The study emphasizes the importance of guiding families towards responsible and moderate use of social media, educating women on how to deal with extortionists, increasing awareness about electronic extortion, its forms, motivations, justifications, and ways to confront it.